Critical Components of a Summer Enrichment Program for Urban Low-Income Gifted Students. (January 2015) - Kaul, Corina R.; Johnsen, Susan K.; Witte, Mary M.; Saxon, Terrill F.
Effective program models are needed for low-income youth. This article describes one successful summer enrichment program, University for Young People's Project Promise, and outlines three key components of a Partnership for Promoting Potential in Low-Income Gifted Students (Partnership Model), which is based on Lee, Olszewski-Kubilius, and Peternel's model. The Partnership Model provides a multi-generational perspective and framework for designing and enhancing summer enrichment programs.